Tourism of Ukraine as a Type of Business before and during the War - YASNOLOB, Ilona; DEMIANENKO, Nataliia; GALYCH, Oleksandr; GORB, Oleg; YEHOROVA, Olena; LIPSKYI, Roman; BOROVYK, Tetyana; MYKOLENKO, Inna; PROTSIUK, Nataliia (Journal of Environmental Management and Tourism, 2023)
Ukrainian tourism as a type of entrepreneurship before and during the war was analyzed in the article. It has been noted that Ukraine is a hospitable country, endowed with incredible nature, ancient culture and has delicious food. But since February 24, 2022, the country has completely lost inbound tourist traffic, business tourism came to a halt, and local tourism turned into the migration of internally displaced persons. It has been determined that the longer the war in Ukraine continues, the more Europe suffers from it as well. Accordingly, the slogan “Stand with Ukraine”, which sounds like the call for help, was proposed to be transformed into “to visit and help”. It has been studied that great opportunities will open up for inbound tourism after the war. At first, routes related to the war and remarkable post-war locations will be relevant. At the same time, the beauty and hospitality of Ukraine will attract tourists. After the victory, Ukraine will be among the top five countries in the world attractive to visit. The sky is open, or at least nominally safe.